Os discursos globalizados do empreendedorismo social: narrativas heroicas, mundos possíveis e consumo simbólico - Sinato, Angelina (2016)
The objective of this study t is to analyze the global discourse of the social entrepreneurship scene. Therefore, we use the methodology of critical discourse analysis (FAIRCLOUGH, 2001) and (VAN DIJK, 2003) on social entrepreneurs life narratives to understand their social role in contemporary society. The object is the narratives present in digital media, which constitute the image of social entrepreneurs worldwide institutions: Ashoka, Skoll Foundation and Schwab. These organizations articulate new possible worlds (LAZZARATO, 2006) and represent in an emblematic way the new spirit of capitalism (BOLTANSKI and CHIAPELLO, 2009). Moreover, attribute legitimacy to social entrepreneurs, who are seen as modern Olympians, true culture models (MORIN, 2011). The social entrepreneur, in summary, joins the competence as a regular entrepreneur with dedication to work for the "common good". The pragmatism of the entrepreneurial figure combines heroic characteristics, which are the symbolic power (BOURDIEU, 2005). This process occurs through a complex network of production, circulation and consumption of these globalized symbolic heroic narratives. From the spread of the phenomenon of social entrepreneurship, we seek to understand their origin, their rhetoric constitution and how the social and cultural aspects are linked to it, as the process of celebritization (TORRES, 2014) the figure of the social entrepreneur.